Self-Efficacy and Technology Adoption for Micro, Small and Medium Enterprises: An Integrated Model of Task-Technology Fit and Technology Acceptance - Victorina Rosette Mantik, Tirza; Debora Kandouw, Dominic; Gabriella Karouwan, Nadya; Rinawati Simanjuntak, Evi (Journal of World Science, 2024)
The development and digitization of the MSMEs ecosystem are accelerated steps towards realizing digital MSMEs that have an impact on the country's economy in the digital transformation era. This study aims to determine self-efficacy, which is an external variable, and technology adoption by MSMEs when implementing the integration of two technological models, namely task-technology fit (TTF) and technology acceptance (TAM), in their business activities. Data were collected through a questionnaire survey distributed to 269 MSMEs using convenience sampling and analyzed using PLS-SEM. The findings of this study indicate that self-efficacy has a greater influence than TTF on perceived ease of use, and the hypothesis about the components of TTF and TAM are supported based on the data on attitudes towards and intentions to use them. This study provides practical recommendations for stakeholders to empower MSMEs and for MSMEs themselves to leverage technology adoption in their business activities. The implications of this research provide practical recommendations for stakeholders to strengthen Micro, Small, and Medium Enterprises (MSMEs) and enhance the adoption of technology in their business activities, thereby driving the growth of the country's economy in the digital transformation era.